Salmonella infection among the pediatric population at a tertiary care children’s hospital in central Nepal: a retrospective study - Pokhrel, Nayanum; Chapagain, Ramhari; Thakur, Chandan Kumar; Basnet, Ajaya; Amatya, Isha; Singh, Rajan; Ghimire, Raghav (Frontiers in Microbiology, 2023)
Background Typhoid fever, an infective bacterial disease is capable of causing fatal systemic infection in humans, and in an era of antimicrobial resistance, it has become of public health importance. This study aimed to investigate the laboratory diagnosis of Salmonella bloodstream infection, its serotype, antimicrobial resistance pattern, and seasonal variation at a tertiary care children’s hospital. Methods We undertook a retrospective, cross-sectional study by reviewing hospital-based laboratory records of patients, whose blood culture samples were submitted from the outpatient department to the laboratory of a tertiary care children’s hospital in Kathmandu, Nepal from January 2017- January 2019. Results Among the total blood culture samples obtained (n=39,771), bacterial isolates (n=1055, 2.65%) belonged either to the genus Enterobacteriaceae or genus Acinetobacter. Altogether (n=91, 8.63%) isolates were positive for Salmonella spp. which were further identified as Salmonella enterica subsp. enterica ser. Typhi (n=79, 7.49%), Salmonella enterica subsp. enterica ser. Paratyphi A (n=11, 1.04%), and Salmonella enterica subsp. enterica ser. Paratyphi B (n=1, 0.1%). The median age of patients was 6 years (IQR: 4-9) with males and females constituting (n=53, 58.24%) (OR, 1.0; 95% CI, 0.60-1.67) and (n=38, 41.76 %) (OR, 0.98; 95% CI, 0.49-2.05) cases respectively. The disease was observed throughout the year with a high prevalence towards the spring season (March-May). Antibiogram showed resistance more towards nalidixic acid with S. Typhi, comprising half the isolates (n=52, 65.82%) (p=0.11). Resistance towards β-lactams with β-lactamase inhibitors (amoxicillin-clavulanate) (1.27%) was seen in a single isolate of S. Typhi. Multidrug resistance pattern was not pronounced. The multiple antibiotic resistance (MAR) index was in the range between 0.14-0.22 in S. Typhi and 0.22-0.23 in S. Paratyphi. Conclusion S. Typhi was the predominant serovar. Infection was common among children between 1 to 5 years of age showing male predominance with spring season contributing to fairly more number of cases. Antimicrobial susceptibility testing of S. Typhi showed more resistance towards nalidixic acid with only a single isolate resistant to β-lactamase inhibitors (amoxicillin-clavulanate). Alarming multidrug resistance patterns were not observed. MAR index in this study indicates the importance of judicious use of antimicrobials and hospital infection prevention and control practices.